1995
DOI: 10.1161/01.str.26.10.1787
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognosis of Stroke in the Belluno Province, Italy

Abstract: Our first-year results confirm the fairly high risk for stroke in central and northern Italy and support European findings regarding risk factors for stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
99
4
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 37 publications
23
99
4
6
Order By: Relevance
“…The use of DRG14 for the selection and identification of acute stroke services presents a limitation due to the possible misuse of ICD classification [10]. Nevertheless our national and regional data on the distributions of DRG14 are in line with recent epidemiological studies on the incidence of stroke in Italy [11][12][13][14]. The methods of data collection by direct local interview with the head of each service and the accuracy and consistency of the results support the validity of our methodological approach.…”
Section: Discussionsupporting
confidence: 77%
“…The use of DRG14 for the selection and identification of acute stroke services presents a limitation due to the possible misuse of ICD classification [10]. Nevertheless our national and regional data on the distributions of DRG14 are in line with recent epidemiological studies on the incidence of stroke in Italy [11][12][13][14]. The methods of data collection by direct local interview with the head of each service and the accuracy and consistency of the results support the validity of our methodological approach.…”
Section: Discussionsupporting
confidence: 77%
“…The prevalence of vascular risk factors in the investigational cohort was roughly similar to that in overall Italian patients with ischemic stroke or myocardial infarction as regards smoking habit, hypertension, and hypercholesterolemia, whereas the prevalence of diabetes or atrial fibrillation was about half that in the general surveys. [24][25][26] Inherited or acquired thrombophilia was investigated in only 142 patients, being present in 29.5% of them with the positive results balanced between patients with polycythemia vera or essential thrombocythemia. Mild hyperhomocysteinemia was found in eight patients, antiphosholipid antibodies in six, inherited thrombophilia in 20, and a combination of inherited thrombophilia and antiphospholid antibodies or hyperhomocysteinemia in eight.…”
Section: Study Patientsmentioning
confidence: 99%
“…Studies reported earlier state that hemorrhagic stroke has higher mortality risk than ischemic strokes. [11][12][13][14][15][16][17][18][19][20] To our knowledge, current study is the first to assess the effect of PNF exercises on functional outcome and QoL in acute stroke. Paolucci et al 21 have stated that the patients with hemorrhagic stroke have better functional prognosis but the other prognostic factors, such as stroke origin, stroke severity, age, and onset to origin interval strongly affect the functional outcome.…”
Section: Discussionmentioning
confidence: 95%